Magnet® Supporting Our Purpose. (October 2022) - Pappas, Sharon; Erickson, Jeanette Ives
ABSTRACT: The authors, Magnet ® Commissioners, provide a reflection on their personal journeys in leading healthcare organizations where the role of nurses is valued by both the organization and those we serve. The authors believe that nurses, through the application of evidence-based leadership principles, are the cornerstone of passion and commitment to excellence in healthcare.